Boron Subphthalocyanines and Silicon Phthalocyanines for Use as Active Materials in Organic Photovoltaics. Issue 6 (23rd January 2019) - Grant, Trevor M.; Josey, David S.; Sampson, Kathleen L.; Mudigonda, Thanmayee; Bender, Timothy P.; Lessard, Benoît H.
Abstract: Organic photovoltaics (OPVs) have experienced continued interest over the last 25 years as a viable technology for the generation of power. Phthalocyanines are among the oldest commercial dyes and have been utilized in some of the earliest examples of OPVs. In recent years, the use of boron subphthalocyanines (BsubPcs) and silicon phthalocyanines (SiPcs) has attracted a flurry of interest with some examples of fullerene‐free devices reaching power conversion efficiencies >8 %. Unlike other more common divalent phthalocyanines such as copper or zinc, BsubPcs and SiPcs contain additional axial groups that can easily be functionalized without significantly affecting the optoelectronic properties of the macrocycle. This handle facilitates our ability to tune the solid‐state arrangement and other physical characteristics such as solubility ultimately giving us the ability to improve the thin film processing and final device performance. This review covers recent studies on the development of BsubPcs and SiPcs for use as active materials in organic photovoltaics. Abstract : Phthalocyanines are among the oldest commercial dyes and they have been utilized in some of the earliest examples of organic photovoltaics (OPVs) due to their ease of synthesis and chemical stability. Boron subphthalocyanines (BsubPcs) and silicon phthalocyanines (SiPcs) have attracted great interest with some examples of fullerene‐free devices reaching power conversion efficiencies >8 %. This review covers recent studies on the development of BsubPcs and SiPcs for use as active materials in OPVs.